Avaliação do plasma frio no processamento de alimentos: efeito na composição do óleo de milho e utilização na modulação do aroma de suco de laranja - Araújo, Aislan Baden da Conceição (2022)
Cold plasma has been studied as an alternative technology to thermal processes in the food industry, but its ability to accelerate lipid oxidation in foods has already been reported, which may be a problem for the use of this technology. In addition, plasma demonstrates the ability to change the composition of volatile compounds in juices, opening up the possibility of using this technology to modulate the aroma of juices. The objective of the research was to study the effect of plasma on corn oil in order to understand how it affects the composition of fatty acids and their quality and understand the effect of plasma on the aroma and volatile compounds of orange juice. Corn oil and orange juice were exposed to two types of plasma, glow plasma (GP) and dielectric barrier discharge plasma (DBD). In the DBD plasma, the excitation frequency of the equipment was analyzed and in the GP, the gas flow and the processing time, the presence of water was evaluated for oil processing and the effect of this parameter on the composition was studied. The composition of the oil after processing in the plasmas showed that lipid oxidation of the oil did not occur in any of the conditions studied, it was verified that in the GP and DBD the change in the fatty acid profile indicated that the linoleic acid could be being formed by the hydrogenation of the linoleic acid. With the presence of water, oleic acid had its content increased in a marked way, assuming that the formation of H and OH species contributed to a convergence process for oleic acid through hydrogenation reactions of linoleic acid and dehydrogenation of stearic acid. The absence of lipid oxidation and the absence of a general increase in saturated acid content indicates that cold plasma can be used without decreasing oil quality. The two types of plasma altered the volatile composition of the juice, the compounds that tended to be consumed in the reactions were limonene, 4-terpineol and, to a lesser extent, terpinolene. The compounds that showed a tendency to be formed were α-pinene, Δ-3-carene and carvone. GP in the condition of 30 mL/min for 30 min led to the greatest reduction of 4-terpineol, being a point of interest for the reduction of this off-flavor in orange juice. The DBD in the 600 Hz condition was the one that best preserved the citrus characteristic of the juice, maintaining the same level of limonene as the unprocessed juice and increasing the Δ-3-carene content. Both devices altered the woody note of the orange juice, but small changes were also seen for the herbal, peppery and fruity aroma notes. Thus, both types of plasma showed the potential to alter the juice's aroma and could be used to accentuate desired notes.